Linguistic Representations of God and Evil in The School for God nd Evil Film : A Discourse Analysis: Penelitian - Putra Darma, Virga; Auliana Geovani A.S, Marshella; Zahira Shofa, Nazwa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research examines the construction and differentiation of “god” and “evil” moral identities in the movie The School for God and Evil by applying a Critical Discourse Analysis approach. The analysis focuses on four main aspects: characters' speech styles, intonation patterns, lexical choices, and framing through discourse that reflects ideological discourse. The research data in the form of dialog transcripts of the central characters-Agatha, Sophie, Professor Dovey, Lady Lesso, and Rhian-are examined using Fairclough's three-dimensional framework (text analysis, discourse practices, and social practices) as well as van Dijk's positive self-presentation and negative otherpresentation strategies. The findings reveal that the “god” character displays reflective speech with stable intonation and empathic diction, while the “bad” character uses short, dramaticallytoned utterances with diction that emphasizes power. This combination of verbal strategies and multimodal elements systematically reproduces moral dichotomies and shapes the construction of audience perceptions. This finding confirms the role of film discourse as an ideological tool in the cultivation and reproduction of moral values.